Survey about public perception regarding smart grid, energy efficiency & renewable energies applications in Qatar. (February 2018) - Abdmouleh, Zeineb; Gastli, Adel; Ben-Brahim, Lazhar
Abstract: In a low-carbon and sustainable future, smart grids have a key role to play not only in saving energy with demand and supply-side management of energy systems, but also in optimizing the integration of a wider range of generation and storage options including renewable energy sources. Moreover, some challenges can follow the transition from a traditional grid into a smart grid. In this context, "public attitude" and "public acceptance" are major components to make more radical scenarios about the feasible implementation of smart grid technologies and successful integration of renewable energy sources. This paper presents unique survey results of public attitudes towards smart grids, smart meters, renewable energy and environment in Qatar using a representative panel from Qatar University community. It contributes to the literature by providing a better understanding of electricity consumers' perception and behavior about the possible deployment of smart grid applications. It also aims to create data about public attitudes to inform policy makers, the business community and other stakeholders for decision-making by introducing institutional and regulatory changes, and modifying the relationship between consumers, the government and utilities. The main conclusions can be used as a basis for sustainable energy planning, and awareness campaigns formulation in order to enhance public acceptance regarding renewable energy projects and smart grid technologies. However, the results are a first attempt to elicit public views and will need to be extended to the larger community in Qatar and repeated at regular basis.